SQ4R METHOD AND READING COMPREHENSION DEVELOPMENT AMONG THE SOPHOMORE BUSINESS STUDNETS - Panjaitan, Nelson B.; Palandeng, Rachel (Journal of Language Pedagogy, 2011)
ABSTRACT: This paper is an experimental study that involves the Sophomore English studentsâ of Business Department of Adventist University of Indonesia Bandung was the subject of the research. The purposes of this study is to find whether there is a significant improvement by using SQ4R method on the Business students, and to describe the advantages and the weakness of the SQ4R method based on research result. The people who have used the SQ4R method said that SQ4R is one of the simple ways in reading comprehension, because by using this method they could spend their time more efficiently to grasp and storage the main ideas easily. The researcher uses the pre-test and the post-test as the instrument. And the data is analyzed by using the T-test in computer. The result shows that tcounted = 2.5 > ttable â 1.96 with significant level 0.025 and the degree of freedom is 30 (df = N1+N2-2). This result means that the SQ4R method is significantly improved the students reading comprehension.